Beratung von Opfern rechter und rassistischer Gewalt: Herausforderungen sozialer Arbeit zwischen individueller Hilfe und politischer Intervention - Köbberling, Gesa (Kultur und soziale Praxis, 2018)
How can those affected by right-wing and racist violence in Germany be supported? Gesa Köbberling utilises results from international hate crime research to reconstruct the connection between individual consequences of violence and their social context using case studies and qualitative interviews. She sketches the potential - but also the limits - of a kind of professional support service that explicitly understands itself as a social and political practice. The study ties in with discussions on the possibilities of a critical practice of social work that does not exclude the political in the idea of the social.